Factors Influencing The Occurrence of Rework In Terms of Risk-Based Communication Management in Construction Projects - Mayniana, Virani; Machfudiyanto, Rossy Armyn (Smart City, 2023)
Rework in a construction project is an unplanned and unwanted activity that requires an action to repeat part or all the work to meet project standards or requirements and, in its implementation, causes increased work, time, and costs. Based on previous studies that discuss the factors that cause rework, poor communication management or coordination between stakeholders is one of the causes of rework. Therefore, a literature study was conducted to identify project communication management risks that allow rework to occur and resulted in 54 communication management risk factors. Furthermore, the results of the literature study were validated by experts who have more than 10 years of experience in the construction field. As a result of the validation, there were 48 communication management risk factors that could cause rework.